Evaluation of experimental vaccination in chinese goose (Anser cygnoides) against newcastle disease: Investigation of the state of virus carrier - Campioni, Josie Maria [UNESP] (2009)
This study aimed the characterization of the importance of vaccination against Newcastle disease in Chinese geese (Anser cygnoides) and to investigate the state of carrier of the virus in this species. There were used 120 Chinese geese, distributed at random into 4 groups, vaccinated or not. At 60 days of age, all groups were challenged with a pathogenic virus (NDV) suspension, EID 50= 10 8.15/0.1 mL and a group of Specific Pathogen Free (SPF) chickens were used as control of the virus. Cloacal and tracheal swabs were collected after 6, 10 and 20 days post-challenge for genome viral excretion by RT-PCR (reverse transcriptionpolymerase chain reaction). Chinese goose of all groups did not demonstrate any signs of Newcastle disease. They were refractory to the clinical disease with the NDV. In Chinese geese from control group, NDV genome was detected 20 days after challenge. It was demonstrated therefore the state of carrier of NDV by Chinese goose. In geese, from the vaccinated groups, genome viral excretion was not detected by RT-PCR. It was also demonstrated the importance of the vaccination in the suppression of the state of carrier of NDV in Chinese geese. © Asian Network for Scientific Information, 2009.